Reconsidering the 30% Gender Quota: A Feminist Legal Analysis of Women's Parliamentary Representation in Indonesia - Raju Moh Hazmi; Nurul Adhha; Sari Sari; Ade Mulyawan (JUSTISI, 2026)
This study examines the ratio legis underlying the 30% quota for women’s parliamentary representation and the causal dimensions of this figure not being met. Why was 30% set as the benchmark for female representation in parliament? Has 30% female representation in parliament been achieved in Indonesia's legislative elections? If not, why is this the case? The method Framed within a normative paradigm, the study analyzes primary/secondary/tertiary legal documents through philosophical, conceptual, and legislative approaches, applying a qualitative, explanatory–descriptive analysis. Novelty the present study will examine the ratio legis that underpins the 30% representation figure, and the causal factors that contribute to the failure to meet this figure. The following analysis will employ a radical feminist legal theory. The analysis that follows consolidates the relevant research landscape. The Results A thirty-percent threshold for women’s participation is in place adopted by Indonesia is not a 'magical a priori' figure, but rather a minimum policy threshold that has emerged from mainstream global norms, supported by human rights obligations (CEDAW), and has an epistemological foundation regarding how numbers affect institutional dynamics (anti-tokenism). The causal justification for the failure of the 30% quota is influenced by a number of factors, including patriarchal culture, party pragmatism and legal structures. The Conclusion the 30% ratio is intended as a corrective tool to shift from formal equality to substantive equality by creating a critical mass so that women's voices are not merely tokenistic. The failure of this threshold reveals a pseudo-neutral legal structure quotas in Indonesia bind candidate lists (descriptive representation) in an open list proportional system without locking in seats (substantive representation), allowing structural barriers political costs, patronage networks, and masculine culture to persist.